Viability of Trichomonas vaginalis in Transport Medium - Beverly, A. L. (American Society for Microbiology, 1999)
The ability of Amies gel agar transport medium to maintain the viability of Trichomonas vaginalis was determined by comparing transported vaginal specimens to specimens immediately inoculated into culture medium. The prevalence of trichomonosis in the study population was 26% (68 of 260 women). The immediate inoculation method detected infections in 64 of 68 infected women (sensitivity of 94.1%). The transport method detected 62 of 68 infections (sensitivity of 91.2%). There was no significant difference between the two methods.